2 - What Has Worked or Failed with Feminist Scholarship in Academic Spaces in Africa? The Case of the School of Women & Gender Studies, Makerere University - Kirungi, Jackline (Journal of Higher Education in Africa, 2022)
Gender inequality remains pervasive in Africa, despite the proliferation of scholarship on feminism on the continent. Yet over the last two decades, progressive intellectual arguments for feminism in Africa have contended that addressing patriarchal practices that underlie gender inequality was paramount to productivity and efficiency emphasised in development projects. In this light, this study explored the transformative potential of feminist scholarship at the School of Women & Gender Studies at Makerere University. It illuminates the politicisation of gender and sexual relations through thought-provoking forums and the pro-women principles contributing to aspirations of feminism scholarship in Uganda. Nonetheless, ongoing scholarship needs to ensure that feminist scholarship philosophies adjust to represent the experiences and struggles of women and their communities in Uganda. The research was qualitative in approach. It employed purposive sampling, participant observation, and consequently interpretive analysis. Data from eight key informative interviews with founders of the school, senior teaching and administrative staff, a d PhD graduate students, as well as document review, informed the study.